Radiometric survey of natural radioactivity concentration and risk assessment on dwellers around Ijako active dumpsite in Ogun State. Issue 1 (February 2021) - Adagunodo, T.A.; Enemuwe, C. A.; Usikalu, M.R.; Orosun, M. M.; Adewoyin, O.O.; Akinwumi, S.A.; Oloke, O.C.; Lukman, A.F.; Adeniji, A.A.; Adewoye, A.O.
Abstract: Radiometric assessment of natural radioactivity concentration around Ijako dumpsite was done using hand held gamma spectrometer. A total of 10 in situ measurements were taken at the site. The U-238, Th-232, and K-40 radioactivity concentration obtained were used to assess the radiological hazard level in the area. Comparing the mean results of radiological parameter obtained with world average; Radium equivalent was far less than 370Bqkg-1, External hazard was less than 1, Annual effective dose equivalent was less than 0.08mSvy-1, Gamma index was less than 1, and Excess life cancer risk was less than 0.29 × 10-3. This implies that Ijako dumpsite poses no radiological hazard to the general public.